Factors for the Formation of a Culture of Dialogue-Based Relationships in the Process of Developing Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
this article comments on the factors, requirements for improving the quality of education, improving the educational system with an emphasis on advanced foreign experience, the effective use of modern pedagogical technologies in teaching, especially adapting students from early, elementary grades to communication, taking education on the basis of friendly forms and methods.